Primary EU law and private law concepts / edited by Hans-W Micklitz, Carla Sieburgh. - Micklitz, Hans-W; Sieburgh, C. H. (Intersentia, 2017)
Primary EU Law and Private Law Concepts starts with the hypothesis that the European Court of Justice has developed concepts in private law cases which differ in substance from the concepts that exist in the private law systems of the Member States. It aims to present developments in the current law of which EU lawyers and private lawyers generally are unaware. It offers ground-breaking analyses of the main private law concepts (the person, property, contract and tort and remedies) as they are used, created or adjusted by the Court. Each analysis results from insights obtained from the substantive meaning of the concepts deployed in the Court's case law, disconnected from the national meanings of such concepts. The direction of this analysis is from the cases to the concepts, not the other way around: the cases and the facts behind the private law relationships are the starting point. In this way the analyses show in detail how primary EU law influences private law relationships. This book will be useful for academics, practitioners and students interested in EU private law. 'EU law's very identity is shaped by its conferral of rights and obligations on individuals but it has conventionally been public law, not private law, that has been the main site for engagement between EU and national law. This collection redresses that imbalance, and shows how primary EU law has induced mutation in concepts of private law. The law of the internal market is inevitably at the forefront, but so too is the protection of fundamental rights.' Stephen Weatherill, Jacques Delors Professor of European Law, University of Oxford 'This is a ground-breaking book. [The editors'] approach presents important results both for legal scholarship and legal practice and underlines the necessity of more cooperation between EU law and private law scholars.' Arthur Hartkamp, Professor of European Private Law, Radboud University, Nijmegen Carla Sieburgh is a Research Professor in Private Law at Radboud University Nijmegen, and an expert in the law of obligations and the interaction of EU law, human rights and private law. Hans-W. Micklitz is Professor of Economic Law at the European University Institute and Distinguished Professor of the Academy of Finland at the University of Helsinki. He has also been a visiting professor at the University of Michigan Ann Arbor and the Somerville College at the University of Oxford. He holds degrees in law and sociology. Intersentia Intersentia